Changing farmer and veterinarian behaviour around antimicrobial use. (2nd March 2019) - Morgans, Lisa; Reyher, Kristen K.; Barrett, David C.; Turner, Andrea; Bellini, Jenny; Elkins, Phil; Clarke, Tom
Abstract : Slowing the development of antimicrobial resistance (AMR) requires reducing antimicrobial use (AMU), which necessitates altering prescribing practices and reducing use in food-producing species (O'Neill, 2015 ;World Health Organisation, 2018 ). The literature has suggested for many years that we should try a different approach to changing practices on farm (Chambers et al, 1985 ) and calls for more farmer-led initiatives compared with traditional, passive knowledge transfer that commonly occurs in the veterinary profession (Escobar et al, 2013 ;Kristensen and Jakobsen, 2011 ;Vaarst et al, 2017 ). When it comes to complex issues such as reducing AMU, a farmer-led approach is well positioned to help farmers and veterinary surgeons change their practices. We propose a farmer-led approach has a key role to play in changing behaviour and helping to solve complex challenges such as AMR.